2020
DOI: 10.1177/0961203320928421
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in adults with primary antiphospholipid syndrome: findings from a mixed-methods study

Abstract: Objective This study aimed to explore the experience and impact of fatigue in adults with primary antiphospholipid syndrome (pAPS). Methods This sequential, explanatory mixed-methods study enrolled adults with a six-month or more history of pAPS. Consenting participants completed the Functional Assessment of Chronic Illness Therapy–Fatigue subscale (FS), Multi-Dimensional Perceived Social Support Scale, Patient Health Questionnaire (PHQ9), Pittsburgh Sleep Quality Index (PSQI), International Physical Activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…We identified that female sex, pain, mental health and functional ability showed a consistent association with fatigue when examined cross-sectionally and predicted people more likely to belong to the Fatigue group. This concurs with findings from another study [ 32 ] and is mirrored in people with inflammatory and non-inflammatory diseases, including post-viral fatigue and post-chemotherapy fatigue [ 33 , 34 ]. Interestingly, many RA-related characteristics such as inflammation and duration of disease were not consistently significantly associated with fatigue cross-sectionally and longitudinally in our analyses [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…We identified that female sex, pain, mental health and functional ability showed a consistent association with fatigue when examined cross-sectionally and predicted people more likely to belong to the Fatigue group. This concurs with findings from another study [ 32 ] and is mirrored in people with inflammatory and non-inflammatory diseases, including post-viral fatigue and post-chemotherapy fatigue [ 33 , 34 ]. Interestingly, many RA-related characteristics such as inflammation and duration of disease were not consistently significantly associated with fatigue cross-sectionally and longitudinally in our analyses [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms the importance of social support for people with long term conditions (Bearne et al., 2020). People with fibromyalgia experience low levels of social support and significantly more loneliness than people with other Rheumatic diseases (Kool & Geenen, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, patients with APS are sometimes afflicted with irreversible damage to the heart, lungs, kidneys, and other organs, resulting from progressive dysfunction and occlusion of the microvasculature. Therefore, it is not surprising that more than 60% of patients with primary APS reported severe fatigue in a recent study (6). Despite the burdens that come with a diagnosis of APS, patient-reported outcomes (PROs) have not been routinely incorporated into clinical care or research protocols.…”
Section: Introductionmentioning
confidence: 99%